The Effect of Turmeric Leaf (Curcuma Longa L.) Extract on Acyl Ghrelin, Growth Hormone, and Ampk Levels in Hyperlipidemic Rats Induced by A High-Fat Diet and Propylthiouracil: An in Silico and in Vivo Study - Grace Stefani Christanto; Endy Juli Anto; Jekson Martiar Siahaan (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hyperlipidemia is a major risk factor for cardiovascular disease, with a continuously increasing prevalence worldwide. Turmeric leaves (Curcuma longa L.) contain various bioactive compounds with potential antihyperlipidemic properties through modulation of metabolic biomarkers such as acyl ghrelin, growth hormone (GH), and AMP-activated protein kinase (AMPK). To analyze the effects of ethanolic turmeric leaf extract on acyl ghrelin, GH, and AMPK levels in hyperlipidemic rats induced by a high-fat diet (HFD) and propylthiouracil (PTU) using combined in silico and in vivo approaches. This laboratory experimental study used Federer's formula to determine the sample size, resulting in 36 male Wistar rats randomly divided into six groups: normal control (K1), hyperlipidemia control receiving HFD+PTU (K2), positive control receiving HFD+PTU+simvastatin 0.9 mg/kg body weight (BW) (K3), and three treatment groups receiving HFD+PTU plus ethanolic turmeric leaf extract at doses of 300 mg/kg BW (K4), 600 mg/kg BW (K5), and 1200 mg/kg BW (K6). In silico molecular docking was conducted to evaluate interactions between active compounds and target proteins. Measured parameters included lipid profiles, aortic histopathology, and levels of acyl ghrelin, GH, and AMPK assessed using ELISA. Phytochemical screening confirmed the presence of five classes of bioactive compounds in the extract. In silico analysis identified rutin as the principal compound, exhibiting strong binding affinities to acyl ghrelin (−10.6 kcal/mol), growth hormone (−8.0 kcal/mol), and AMPK (−9.3 kcal/mol). The 300 mg/kg BW dose demonstrated the most pronounced lipid-lowering effects, with significant reductions in total cholesterol (210.50±2.74 to 181.67±6.98 mg/dL), triglycerides (246.83±8.47 to 179.17±8.80 mg/dL), and LDL (96.33±5.68 to 70.17±8.11 mg/dL), alongside an increase in HDL (65.00±3.74 to 75.67±1.97 mg/dL) (p<0.001). Histopathological analysis revealed reduced aortic wall thickness (192.59±6.99 μm) and foam cell count (24.17±4.31) in this group. Acyl ghrelin levels differed significantly among groups (p<0.001), with the hyperlipidemic control showing the lowest levels. The 600 mg/kg BW dose optimally increased AMPK (10.33±0.95 ng/mL) and GH (1.96±0.15 ng/mL) compared with the hyperlipidemic control (p<0.05). Ethanolic turmeric leaf extract exerts significant antihyperlipidemic effects by improving lipid profiles, attenuating atherosclerosis, and modulating metabolic biomarkers including acyl ghrelin, GH, and AMPK. A dose of 300 mg/kg BW was most effective for lipid profile improvement and atherosclerosis reduction, while 600 mg/kg BW was optimal for hormonal biomarker modulation.